Inuit boy (Tom Luce) on board whaling schooner Era, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1897)
An Inuit boy identified as Little Tom Luce is on board the whaling schooner Era in Hudson Bay, Canadian Arctic, [ca. 1897-1905]. He is wearing a cap and checked overalls. Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo 155, #106. Number 106 is etched into the emulsion on lower part of plate. The boy was named after the owner of the whaling schooner Era. The schooner Era was built in 1847 at Boston, Massachusetts. She was a New London whaling vessel until her last voyage out of that port in 1892; her masters included James Monroe Buddington, John O. Spicer, and George Comer. She was wrecked off Miquelon Island, July 27, 1906. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels, including the Era, from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.